2019
DOI: 10.3390/foods8070253
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptability, Eye Fixation, and Physiological Responses: A Study of Novel and Familiar Chocolate Packaging Designs Using Eye-Tracking Devices

Abstract: Eye fixations on packaging elements are not necessarily correlated to consumer attention or positive emotions towards those elements. This study aimed to assess links between the emotional responses of consumers and the eye fixations on areas of interest (AOI) of different chocolate packaging designs using eye trackers. Sixty participants were exposed to six novel and six familiar (commercial) chocolate packaging concepts on tablet PC screens. Analysis of variance (ANOVA) and multivariate analysis were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
4
24
0
2
Order By: Relevance
“…In the case of the correlations among the self-reported and subconscious responses (Figure 2b), it was found that consumers rate labels as higher quality when they perceive coffee as higher strength, when labels are more pleasant, and when they elicit more positive emotions; the latter is consistent with findings from Gunaratne et al [2] for chocolate label assessment. Furthermore, the willingness to purchase is directly influenced by the perceived quality, as found in other research [33].…”
Section: Multivariate Data Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…In the case of the correlations among the self-reported and subconscious responses (Figure 2b), it was found that consumers rate labels as higher quality when they perceive coffee as higher strength, when labels are more pleasant, and when they elicit more positive emotions; the latter is consistent with findings from Gunaratne et al [2] for chocolate label assessment. Furthermore, the willingness to purchase is directly influenced by the perceived quality, as found in other research [33].…”
Section: Multivariate Data Analysissupporting
confidence: 87%
“…Following the results from the emotional and emoji responses, the premium label was highlighted with statistically higher areas of interest selection, such as colors, layout, and pattern/texture, with layout being the highest area of interest for the natural concept and color for the bold concept (Table 6). However, analysis of features was limited in this study; more specific assessments can be conducting when analyzing label features using eye-trackers [2,3,[27][28][29] or more practically for virtual sensory sessions when using digital tools (from video analysis) for eye tracking to assess fixation number and duration that the panelists spend at each component [30,31]. The DAFW group has developed algorithms to analyze eye-tracking parameters and the emotional response based on facial expressions from the different features of labels [32].…”
Section: Analysis Of Areas Of Interest Within Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the influence of emotions in decision-making, especially for new food products and even food packaging for consumer acceptability [ 15 , 16 , 18 , 19 , 20 , 21 ], it is important to assess how insect-based food products make consumers feel, besides studying only their acceptability. Therefore, some studies have been conducted to evaluate emotional responses towards foods with insects [ 22 ], specifically focused on disgust [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers noted that while simple elements and sharp edges showed higher attention and valence, higher valence was observed for pictorial images as opposed to computer-generated images [64]. A study on chocolate packaging did not find any significant differences in AFEA data for the experimental package images [65].…”
Section: Differentiation Of Stimuli By Expressed Emotionmentioning
confidence: 96%